2012
DOI: 10.1177/0267323112459433
|View full text |Cite
|
Sign up to set email alerts
|

Female bestsellers: A cross-national study of gender inequality and the popular–highbrow culture divide in fiction book production, 1960–2009

Abstract: This article studies trends in gender inequality in the domain of fiction books between 1960 and 2009 in France, Germany and the United States by analysing bestseller lists and literary award winners. It is argued that gender inequality is larger in fields or genres where more status is at stake for individual agents, as this causes an influx of men who then 'edge' women out of the field. The study finds evidence for this mechanism, as the presence of female authors in bestseller lists (exponent of the popular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 43 publications
1
17
0
4
Order By: Relevance
“…They concluded that, in both direct and indirect ways, existing cultural frameworks about art and gender disadvantage 'the amount and type of legitimacy that female artists can accrue' (Schmutz & Faupel 2010, 685). This is consistent with research investigating the experience of French professional artists (musicians, actors and dancers; Coulangeon et al 2005), arts management (Herron et al 1998) and gender inequality in the literary fields (Verboord 2012).…”
Section: Women In Creative Artssupporting
confidence: 89%
“…They concluded that, in both direct and indirect ways, existing cultural frameworks about art and gender disadvantage 'the amount and type of legitimacy that female artists can accrue' (Schmutz & Faupel 2010, 685). This is consistent with research investigating the experience of French professional artists (musicians, actors and dancers; Coulangeon et al 2005), arts management (Herron et al 1998) and gender inequality in the literary fields (Verboord 2012).…”
Section: Women In Creative Artssupporting
confidence: 89%
“…Perhaps because of this, the literary novel emerged in the late 19th century as a separate, less popular but more prestigious male-dominated genre (Tuchman & Fortin, 2012; for a case study, see Corse & Westervelt, 2002;Yaeger, 1987). This continued an evolving trend of gender differences in the typical genres of books written, and women still seem to be under-recognized for the literary value of their works (Verboord, 2012). This extends to many other art fields and is an international phenomenon (Berkers, Verboord, & Weij, 2014).…”
Section: Gender and Authorshipmentioning
confidence: 99%
“…Although many publisher‐related sites have hosted statistics about popular books and some surveys have analyzed the preferences of readers, there do not seem to have been systematic analyses of the popularity of books on a large scale by author gender and genre, other than small scale analyses of bestsellers or literary awards (e.g., Verboord, ). The current article fills this gap using data from Goodreads.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these drivers were explored in the literature [3,4]: they are book critics [5], the author's and fans' circle of friends [6,7], celebrities [8], online reviews [9,10] and word of mouth [11]. The writing style of the author [12,13], the amount of publicity [14], the timing of the book release [15], awardwinning [16] or already bestseller [17] status of the book, the genre of the book and even the gender of the author [18,19] are among the factors considered in past research. Yet, which books become successful and how they reach this status remains a mystery.…”
Section: Introductionmentioning
confidence: 99%